Economic evaluations in migraine: systematic literature review and a novel approach. (2nd August 2020) - Mahon, Ronan; Huels, Jasper; Hacking, Victoria; Cooney, Philip; Danyliv, Andriy; Vudumula, Umakanth; Vadapalle, Sreelatha; Vo, Pamela; Maniyar, Farooq H.; Palmer, Stephen; Goadsby, Peter J.
Abstract: Background: For novel migraine therapies, economic evaluations will be required to understand the trade-offs between additional health benefit and additional cost. The purpose of this study was to conduct a systematic literature review (SLR) to identify previous economic evaluations in migraine from the United Kingdom or Irish perspective to critically appraise these evaluations and to propose, if necessary, a novel modelling approach that can be used for future economic evaluations of migraine therapies. Methods: An SLR was conducted to identify previous economic evaluations of preventive migraine treatments. Key opinion leaders were consulted to determine the criteria for a robust migraine economic evaluation. Economic evaluations identified in the SLR were appraised against these criteria, and a novel cost-effectiveness model structure was then proposed. Results: Eight records reporting on published economic evaluations were identified and critically appraised for general quality. Expert consultation provided 6 recommendations on the ideal model structure for migraine that is both clinically and economically meaningful. A decision-tree plus Markov structure was then developed as a cost-effectiveness model for migraine therapies where each health state is associated with a patient distribution across monthly migraine day (MMD) frequencies. Conclusions: Future migraine economic evaluations should allow for assessments across the full spectrum of migraine, a response-based stopping rule, and the estimation of benefits and resource costs based on MMD frequency. The approach proposed in this paper captures all of the desired elements for an economic evaluation of migraine therapy and is suitable to assess new migraine therapies.